Study Of The Effect of Ions on The Mechanical, Thermal and Spectral Properties of the CoFe2O4 Compound by Chemical Deposition Method - Abdul Samie Fawzi Abdul Aziz; Ali Saleh Jassim (Tikrit Journal of Pure Science)
The preparation of compounds ferrite cobalt Indemnified zinc ions (Zn+2) with the chemical formula (Co1-xZnxFe2O4) values ​​(x = 0.0, 0.2,0.4,0.6,0.8,1) was the study of the mechanical properties of hardness before and after thermal treatment, as it turns out The hardness increases with ion concentration of zinc (Zn+2) as well as thermal treatment increases the amount of hardness, were also studied the thermal properties of the models represented by a factor of thermal conductivity and the amount of heat lost during the time it was found that increasing the concentration of zinc increases the thermal conductivity coefficient and thus lead to an increase heat lost, and the results of infrared spectroscopy showed that the Vibration motor molecules elements and excitement of electronic vehicles (Co1-xZnxFe2O4) Spectrometer IR , which in turn helps to know wavelengths and show that the wavelength of the element iron is located within the range (541-582) cm_1 and cobalt (441-457) cm_1 and element zinc (418-433) cm_1.